The impact of corporate social responsibility on human resource management practices in manufacturing firms in the southern part of Malaysia - Omar, S.S.; Chan, S. W.; Ridwan, M. S.; Ahmad, A. R.; Ariffin, Z. Z. (Research Associations, 2018)
CSR has gained substantial consideration in management circles and have been linked to HRM in various ways. The study on how CSR would affect HRM or the vice versa has been of interest by many scholars. Much has been focusing on the conceptual framework, but very scant on the empirical findings. This study investigates the impact of CSR on HRM practices in the manufacturing industries in the Southern Part of Malaysia. We try to find out how CSR activities impact HRM practices namely recruitment, selection, training, performance appraisal and compensation. Qualitative study was adopted and in-depth face-to-face interview with the HR Managers was implemented. Our result show CSR give impacts toward HRM practices based on several themes that include diversity of the workers, attracting best talent, equality between gender and others. Several implications have been documented.